2021
DOI: 10.5812/aapm.121402
|View full text |Cite
|
Sign up to set email alerts
|

Mirogabalin as a Novel Gabapentinoid for the Treatment of Chronic Pain Conditions: An Analysis of Current Evidence

Abstract: : Neuropathic pain has presented a challenge for physicians to treat and often requires a multimodal approach with both pharmacologic and lifestyle interventions. Mirogabalin, a potent, selective ligand of the α2δ-1 and α2δ-2 subunits of voltage-gated calcium channels (VGCCs), provides analgesia by inhibiting neurotransmitter release at the presynaptic end of the neuron. Mirogabalin offers more sustained analgesia than its gabapentinoid counterparts in addition to a wider safety margin for adverse events. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Both mirogabalin and cebranopadol seem to be potential novel treatment options for neuropathic pain. Although they have been found effective and well-tolerated in clinical trials in patients suffering from various types of chronic and acute postoperative pain [25][26][27][28][29][30][31][32][33][34][35][36][37][38], there is very limited data about their efficacy at the preclinical level, i.e., in some experimental models of pain resulting from drug-induced injuries to peripheral sensory nerves. For this reason, this in vivo research was focused on the assessment of the effects of mirogabalin and cebranopadol on the pain threshold in mice exposed to neuropathy-inducing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Both mirogabalin and cebranopadol seem to be potential novel treatment options for neuropathic pain. Although they have been found effective and well-tolerated in clinical trials in patients suffering from various types of chronic and acute postoperative pain [25][26][27][28][29][30][31][32][33][34][35][36][37][38], there is very limited data about their efficacy at the preclinical level, i.e., in some experimental models of pain resulting from drug-induced injuries to peripheral sensory nerves. For this reason, this in vivo research was focused on the assessment of the effects of mirogabalin and cebranopadol on the pain threshold in mice exposed to neuropathy-inducing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Mirogabalin is the current novel gabapentinoid being explored in the pain field. The drug shows promising results to treat pain conditions with good efficacy and tolerability [200].…”
Section: α2δ Subunit Blockadementioning
confidence: 99%
“…The results indicated that mirogabalin was effective in reducing pain and improving sleep quality. However, it is important to note that mirogabalin is primarily associated with the central nervous system (CNS) side effects, with somnolence, dizziness, and headache being the most commonly reported [ 27 ]. These side effects appear to increase in incidence with higher doses of mirogabalin, although their severity remains relatively constant.…”
Section: Reviewmentioning
confidence: 99%